Evaluasi Kinerja Pengawas Madrasah di Kota Tangerang Selatan dalam Pelaksanaan Kurikulum 2013 menggunakan Discrepancy Evaluation Model - Mu'arif, Mu'arif; Syukur, Muhamad; Azahra, Salsabila (Universitas Negeri Padang, 2025)
This study aims to identify gaps in the performance of madrasah supervisors in implementing the 2013 Curriculum in South Tangerang City using the Discrepancy Evaluation Model (DEM), which focuses on aspects of input, process, and output. The approach is descriptive qualitative, with data collection techniques through interviews, observations, and document studies. Data were analyzed using data reduction, data presentation, and conclusion-drawing techniques. The study results indicate that although supervisors have appropriate academic qualifications, there is nonlinearity with the tasks given, where one MTs supervisor does not yet have a Master's degree, which is a requirement. The performance gap occurs because some supervisors do not set curriculum supervision priorities or detail the coaching program's implementation schedule. Teacher coaching activities are mostly done through MGMP, while class visits and observations are rarely conducted. This problem impacts the less-than-optimal performance of teachers in implementing the 2013 Curriculum, especially in the preparation of learning devices, determination of Minimum Learning Completeness (KBM), implementation of learning, and preparation of assessment instruments. This shows that implementing the 2013 Curriculum in madrasas in South Tangerang City in 2019 is still far from expectations.